การประเมินความเปราะบางของครัวเรือนต่อการจัดการศูนย์ช่วยเหลือผู้ประสบภัยน้ำท่วม: ชุมชนหมู่1พัฒนา เทศบาลบ้านไผ่ จังหวัดขอนแก่น - ชนาภิวัฒน์ ขันทะ (จุฬาลงกรณ์มหาวิทยาลัย, 2020)
This research study investigated and compared the needs of households with different degrees of vulnerability on flood management by the flood relief center. It was intended to provide suggestive information on the flood management. The population of this qualitative research was 231 families in Moonueng Pattana Community. A set of questionnaire with a reliability of 0.812 was distributed to the above households and a total of 111 questionnaires were returned to the researcher. Descriptive statistics including; frequency, percentile, mean and standard deviation were used for data interpretation and explaining social and economical status of the participants. The statistics used in the data analysis were Independent t-test and One-way Anova.It was observed that the various degrees of families’ vulnerability had not been associated with different needs on the flood management. On the average, a moderate level of opinion was observed in both of the topics above. Finding sleeping areas, and finding separated spaces for the vulnerable groups. It was suggested that the flood relief center; provide the households with life-packages for flood evacuation, prepare facilities and place for flood relief and evacuation. It was also advised for the flood relief center to conduct activities to enhance public awareness on the impact of flood on the people lives and properties.